Measurement of exclusive ρ+ρ− production in high-Q2 two-photon collisions at LEP - Dova, María Teresa (2004)
Exclusive ρ+ρ− production in two-photon collisions involving a single highly-virtual photon is studied for the first time with data collected by the L3 experiment at LEP at centre-of-mass energies 89 < √s < 209 GeV with a total integrated luminosity of 854.7 pb−1. The cross section of the process γ γ ∗ → ρ+ρ− is determined as a function of the photon virtuality, Q2, and the two-photon centre-of-mass energy, Wγ γ , in the kinematic region: 1.2 < Q2 < 30 GeV2 and 1.1 < Wγ γ < 3 GeV. The ρ+ρ− production cross section is found to be of the same magnitude as the cross section of the process γ γ ∗ → ρ0ρ0, measured in the same kinematic region by L3, and to have similar Wγ γ and Q2 dependences.